Strengthened to forgive workplace transgressions: priming new money increases interpersonal forgiveness. Issue 8 (10th March 2015) - Mok, Aurelia; De Cremer, David
Abstract We propose that a focus on new money increases forgiveness of others. Three studies provided consistent support for our hypothesis. Working adults recalled an interpersonal offense by a colleague and were subsequently induced to think of either new or used banknotes. Thinking of new (vs. used) banknotes led to weaker destructive tendencies toward the offender (Study 1), more pro‐relationship thinking (Study 2), and higher forgiveness (Study 3). This effect was mediated by feelings of vitality (Study 3), indicating a strength‐based mechanism. We discuss implications for research on money, forgiveness, self‐regulation, and organizational behavior.